Patricia Knapp’s Landmark Project to Develop a Plan of Curriculum-Integrated Library Instruction. A review of: Knapp, P. B. (1966). The Monteith College library experiment. New York, NY: Scarecrow Press. - Carol D. Howe (Evidence Based Library and Information Practice, 2011)
Objective – To create a college-level, four-year plan of library instruction in which assignments directly relate to students’ course work. To develop tools to assess the plan’s effectiveness in improving students’ library skills and contributing to their overall academic success. Design – Exploratory longitudinal cohort study employing pilot library assignments, interviews, and questionnaires. Setting – Monteith College, one of eleven colleges at Wayne State University. Monteith was a small liberal arts college established in 1959 which stressed innovative teaching methods such as team-teaching, small-group discussion, and independent study (Worrell, 2002). Subjects – Teaching faculty from all three college divisions—social sciences, natural sciences, and humanities—and students at Monteith College. Over the course of the study the college employed between 15 and 30 faculty members and enrolled 300 to 700 students. Methods – The project team consisted of project director Patricia Knapp, a project librarian, and a project research analyst. The team worked with the teaching faculty to develop course-related library assignments. Students completed a series of assignments over several semesters as part of their course requirements. The assignment series changed over the course of the project. Students who entered in the fall of 1959 or the spring of 1960 completed Sequence A consisting of six assignments. Students who entered in the fall of 1960 completed Sequence B, six assignments that were a mixture of original and revised assignments. Students who entered in the spring or fall of 1961 completed two revised library assignments.In the summer of 1961, the investigators conducted the first of two small studies. They interviewed a random sample of 21 Monteith students about their experiences with the library and the required library assignments. The students also completed library performance tests such as choosing a subject heading to match a topic or deciphering an entry in a periodical index. This allowed the investigators to compare different measures of library competence and get feedback on the library assignments. In the summer of 1962, the investigators conducted a second small study of 40 Monteith students. The investigators evaluated the tests and other tools used in the first study.The investigators then analyzed student and faculty data collected from Sequences A, B, and C, and from the two sample studies. Data included faculty interviews and feedback from student participants in the sample studies. The investigators also analyzed questionnaire data and the completed student assignments. They analyzed data using nonparametric, small sample statistics. Main Results – Knapp’s results helped shape the final plan of instruction and assessment presented in her book-length published report The Monteith College Library Experiment. It should be stated again that the project objective was not to implement a plan of instruction and assessment but simply to develop one.One of the most important findings was that small sample studies can effectively test the reliability of library assignments. The sample studies allowed the team to “…define and measure library competence and to identify factors associated with its achievement” (Knapp, 1966, p. 17).On a different level, the project offered insight into the faculty-librarian relationship. The investigators found that faculty resisted librarian input into their courses. They also discovered that the most effective group size for developing library assignments was a small group of two to four people, but this sized group was conducive to informal meetings in which key players, often the librarian, were left out. When faculty did not share in decision-making, project morale was low. The project team reorganized and reassigned roles, and the project ran more smoothly.Knapp also learned about the faculty-student relationship. Knapp felt that some faculty simply passed on their knowledge to students rather than teaching students how to acquire it for themselves (Worrell, 2002). She found that student enthusiasm mirrored faculty enthusiasm about library assignments. Early in the project, faculty members presented library assignments to their students. The investigators discerned that both students and faculty were more amenable to the assignments when a librarian presented them and explained their purpose. Knapp (2000) agreed with Bruner who stated in The Process of Education that context is important when teaching any skill; students need to be able to relate the skills they are learning to the importance of why they are learning them (1960).Finally, Knapp learned that students need more than to understand library organization (such as cataloging and classification systems). Students also need to understand “the organization of scholarly communication” to foster true library competence (Knapp, 1966, p. 81). Whereas library organization concerns itself with subject and form, the organization of scholarship “reflect[s] discipline, ‘school,’ concept, and method” (Knapp, 2000, p. 10). Conclusion – The Monteith College Library Experiment ended in 1962 with a thoughtfully planned and tested program of library instruction. The final proposed program included 10 library assignments that were: of increasing complexity and aligned with the curriculum; intellectual with a focus on problem-solving; and feasible within the library’s parameters. Students would complete one or more of the assignments each semester for four years as part of specific course requirements. Knapp noted the program could be adapted to any college curriculum. It would require six years for implementation and assessment. This includes an initial year for planning in which teaching faculty and librarians would collaboratively develop course-related library assignments, four years for student completion of assignments, and a sixth year for assessment.Knapp outlined three levels of assessment. Investigators would assess the appropriateness of individual assignments through interviews and questionnaires collected from faculty and students, as well as completed student assignments. Knapp outlined two ways to assess library competence. First, Monteith faculty members would assess literature reviews in their subject specialties written by second semester seniors. Next, faculty from other Wayne State colleges would review papers from both Monteith and non-Monteith students to comparatively assess the students’ use of sources. Knapp proposed that faculty judgment would be the most valuable measure of the relationship between library competence and overall academic success.Knapp was prepared to implement her plan of instruction using all of her findings, but her proposal to move into phase two of the project was rejected by both the Office of Education, whose members cited economic reasons, and the Council on Library Resources, whose members were not satisfied that faculty were invested in the idea of curriculum-integrated library instruction (Worrell, 2002).